Oxidação lípidica no processo de extrusão em pet food - Ribeiro, Priscila Martins (2018)
Extrusion is a technology widely used in food processing for humans and animals. Even today, little is known about the changes that occur in lipids during food processing. In this research two experiments were carried out to evaluate the oxidative modifications occurred in extruded foods for cats containing poultry fat as lipids source submitted to different SME (specific mechanical energy) and the impacts of these modifications on the shelf-life and its properties. In the experiment one was evaluated the effect of SME fat quality of fat in extruded rations for cats and in experiment two were evaluated different sources of antioxidants on the shelf-life of chicken fat as well as on a extruded food for cats. There was also a significant difference between SME, with the highest values obtained for low SME and the lowest for high SME (P <0.001). A significant difference was observed between the three methods used for lipid extraction (P> 0.001) and the three SME used in the process. There was a relationship between the rupture force and the SME application in the process for the extrudate analysis. The difference in the dry kibble density between the different SME was significant, being the highest density verified in the treatment with low SME (460 g.L-1), followed by medium (390 g. L-1) and high (200 g.L-1), respectively (P <0.001). This same sequence of statistical results was verified for the force of kibble rupture (P <0.001). It was possible to observe that all fatty acids were degraded as the extrusion process progressed (P> 0.001), in particular linoleic acid. Among the four treatments, the antioxidant TBHQ proved to be the most effective for stabilizing chicken oil and rations during processing, reaching a maximum of 1.93 Meq.kg-1. In the palatability test cats showed preference for foods with low IP (P> 0.0195) showing that prevention of lipid oxidation in the process is important. It was observed that the oxidative loss of linoleic acid was more than 50% independent of the SME applied. Antioxidants appear to be fundamental in the protection of fatty acids in extruded foods